THE EFFECT OF TEAM ASSISTED INDIVIDUALLY MODEL IN WRITING NARRATIVE TEXT AT THE EIGHTH GRADE OF SMP NEGERI 1 BARUS IN 2021/2022 ACADEMIC YEAR - Putri Juliana Purba (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract :The purpose of this research to know 1) the application of team assisted individually model in writing narrative text, 2) the students’ ability to write narrative text before and after using team assisted individually model, 3) whether there are any significant effect of using team assisted individually model on students’ writing narrative text. This research used experimental model with the pre-experimental design by using one-group pretest and posttest design. The sample of this research is 28 students of class VIII-B by using purposive sampling. In collected data the researcher used questionnaire and test, the result of research are: 1)application of team assisted individually model was 90 (very good categorized), 2) the mean score of students’ writing narrative text before and after using team assisted individually model was 43 (bad categorized) and 75,5 (good categorized). Differential analysis using “t-test” formula. The result of the analysis show that ttest bigger than ttable(ttest 7.06>ttable2.05). Therefore, the hypothesis is accepted. It means that there is any significant effect of team assisted individually model in writing narrative text at the eighth grade of SMP Negeri 1 Barus. Key Words : Writing, Narrative Text, Team Assisted Individually Model.